Associations of Sex and Household Area with Physical Activity and Sedentary Behavior During Total and Partial Covid-19 Lockdowns in Chile: A Study in Adults Aged 18-44 Years - Marquez-Andrade, J; Vanegas-Lopez, J (Korean Society for Preventive Medicine, 2025)
Objectives: The coronavirus disease 2019 pandemic led to various intensities of lockdowns, affecting lifestyles globally. This study investigates the impact of partial lockdown versus total lockdown on adult physical activity (PA) and sedentary behavior. Methods: A cross-sectional online survey was conducted from April 2020 to October 2020, with 493 participants included in the analysis. Results: The analysis revealed no significant differences in total PA or total sitting time between partial lockdown and total lockdown scenarios. However, moderate physical activity (MPA) significantly decreased during total lockdowns, with more pronounced reductions among females than males. Notably, a positive correlation was found between household area and MPA, suggesting that larger living spaces may encourage more PA. A negative correlation was observed between sitting time and MPA during both types of lockdown. Conclusions: Total lockdown conditions were associated with a significant decrease in MPA, highlighting sex disparities in PA responses. Living space size emerged as a crucial factor in maintaining PA levels during restricted conditions. This study emphasizes the need to consider environmental and demographic factors in public health strategies during prolonged periods of restricted movement. © © 2025 The Korean Society for Preventive Medicine.